2022
DOI: 10.1093/ooec/odac001
|View full text |Cite
|
Sign up to set email alerts
|

Empty digital wallets: new technologies and old inequalities in digital financial services among women

Abstract: Digital financial services (DFSs) may lower certain costs of accessing finance, but they bring new costs, including difficulties accessing mobile networks. Using the Demographic and Health Surveys and several geocoded databases in Nepal, the Philippines, Senegal and Tanzania, this paper studies the distribution of digital finance use among women and its enabling infrastructure, including mobile phone towers, compared to traditional finance. The potential of digital technologies to lessen inequalities depends o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…The estimation results reveal that socioeconomic and demographic factors affecting the probability and frequency of DFS usage include gender, age, education, employment status, residential location, mobile phone ownership, account ownership, and BTS Density. These findings are consistent with several previous studies that found gender (Zins & Weill, 2016), age (Ljumović et al, 2021), education (Maulana & Nuryakin, 2021), employment status (Marumbwa, 2014), urban location (Chamboko, 2022), mobile phone ownership (Lenka & Barik, 2018), ownership of accounts in financial institutions (Maulana & Nuryakin, 2021), and mobile phone towers (Caron, 2022) influence DFS adoption. Efforts to increase DFS demand can be stimulated by providing education to the public regarding digital literacy (through the Ministry of Communication and Information Technology) and financial literacy (through the Central Bank and Financial Services Authority), aligning to provide comprehensive information about the benefits and risks of digital financial access, especially to vulnerable populations excluded from financial services, such as women, the elderly, individuals with low education, the unemployed, rural residents, those without mobile phones, and those without accounts.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The estimation results reveal that socioeconomic and demographic factors affecting the probability and frequency of DFS usage include gender, age, education, employment status, residential location, mobile phone ownership, account ownership, and BTS Density. These findings are consistent with several previous studies that found gender (Zins & Weill, 2016), age (Ljumović et al, 2021), education (Maulana & Nuryakin, 2021), employment status (Marumbwa, 2014), urban location (Chamboko, 2022), mobile phone ownership (Lenka & Barik, 2018), ownership of accounts in financial institutions (Maulana & Nuryakin, 2021), and mobile phone towers (Caron, 2022) influence DFS adoption. Efforts to increase DFS demand can be stimulated by providing education to the public regarding digital literacy (through the Ministry of Communication and Information Technology) and financial literacy (through the Central Bank and Financial Services Authority), aligning to provide comprehensive information about the benefits and risks of digital financial access, especially to vulnerable populations excluded from financial services, such as women, the elderly, individuals with low education, the unemployed, rural residents, those without mobile phones, and those without accounts.…”
Section: Discussionsupporting
confidence: 92%
“…The research by Maulana and Nuryakin (2021) found that account ownership significantly affects the probability of using financial services. The study by Caron (2022) found that the presence of mobile phone towers significantly influences DFS usage in the Philippines, Senegal, and Tanzania.…”
Section: Socioeconomic and Demographic Factors In Dfs Usagementioning
confidence: 99%
“…Studies on micro-level financial behaviour have traditionally focused on access to finance (Caron, 2022; Shabir and Ali, 2022; Ndoya and Tsala, 2021; Mndolwa and Alhassan, 2020; Ghosh and Vinod, 2017; Zins and Weill, 2016; Fungácová and Weill, 2015) with little attention paid [1] to financial resilience. The role of financial literacy on improving financial resilience is gaining traction, particularly in developed countries, however this intervention has been shown to have negligible effects (Fernandes et al , 2014), as on its own, does little to reduce the financial vulnerability of individuals.…”
Section: Background and Contributionmentioning
confidence: 99%
“…Therefore, scholars have conducted a lot of research on the impact of digital finance development. As digital finance is more inclusive and inclusive, it has a significant impact on driving economic growth ( Liu et al, 2021 ), promoting consumption growth ( Li et al, 2020 ), increasing residents’ income ( Wang and Ji, 2022 ), narrowing the urban–rural income gap ( Ji et al, 2021 ), reducing inequality ( Caron, 2022 ), etc. have positive effects.…”
Section: Literature Reviewmentioning
confidence: 99%